1999
DOI: 10.1103/physrevlett.83.2425
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically Constrained Magnetic Wall

Abstract: The structure and properties of a geometrically constrained magnetic wall in a constriction separating two wider regions are studied theoretically. They are shown to differ considerably from those of an unconstrained wall, so that the geometrically constrained magnetic wall truly constitutes a new kind of magnetic wall, besides the well known Bloch and Néel walls. In particular, the width of a constrained wall can become very small if the characteristic length of the constriction is small, as is actually the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
264
2
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(280 citation statements)
references
References 3 publications
10
264
2
4
Order By: Relevance
“…In this paper however we do not make any assumptions on the origin of the pinning, which can be achieved in other ways. One example could be a ferromagnetic body, made by two regions connected through a small constriction: a domain wall is developed in the constriction, when the wider regions are magnetized in opposite directions 9,10 .…”
Section: The Systemmentioning
confidence: 99%
“…In this paper however we do not make any assumptions on the origin of the pinning, which can be achieved in other ways. One example could be a ferromagnetic body, made by two regions connected through a small constriction: a domain wall is developed in the constriction, when the wider regions are magnetized in opposite directions 9,10 .…”
Section: The Systemmentioning
confidence: 99%
“…If Eq. (2) has a DW solution of a boundary condition ∂m/∂n = 0, where n is the normal direction of the wire boundary, it means that a DW is pinned [4,28]. Mathematically, the depinning field is the minimal external field at which Eq.…”
Section: Model and Theoretical Approachmentioning
confidence: 99%
“…Thus, a trap potential as a function of one variable like the DW center is ill defined. A seminal analytical work by Bruno [4] suggests that the pinning can only occur at narrower parts of a constrained nanowire. Thus, it cannot explain DW pinning by an antinotch [18].…”
Section: Introductionmentioning
confidence: 99%
“…As shown by Bruno [1], DWs can be tailored by defining constrictions in a ferromagnetic structure. Garcia et al [2] reported large values of magnetoresistance which were attributed to domain wall scattering due to the inability of electron spin to travel across the DW adiabatically when its length is comparable to the Fermi wavelength [3].…”
Section: Introductionmentioning
confidence: 99%